Electron‐donor substituents on the dppz‐based ligands to control luminescence from dark to bright emissive state in Ir(III) complexes. Issue 12 (24th January 2020) - Dreyse, Paulina; Santander‐Nelli, Mireya; Zambrano, David; Rosales, Luis; Sanhueza, Luis
Abstract: The structures and electronic properties of a series of cyclometalated Ir(III) complexes with substituted dppz ancillary ligand (dppz: dipyrido[3, 2‐a:2′, 3′‐c]phenazine) including tert‐butyl, pyrrolidine ring, and alkoxys substituents as donor group have been theoretically study. With the aim of highlight the attractive qualities of each system for their use as luminescent material, the effects of the electron‐donor substituents onto dppz was evaluated on the structural, charge transport, absorption, and phosphorescent properties. The effect of the substituent was studied on the modulation of the bright and dark triplet states. Main results show that ortho‐methoxy and tert‐butyl substituents act as lower electron‐donating groups, then, efficient electron donation ability was displayed with alkoxy (ethoxy and propoxy) substituents. The best performance was found in a complex with pyrrolidine ring according since their phosphorescence is favored, highlighting their larger electric transition dipole moment value, proposing this system as potential candidate to LEC technology. Abstract : The geometrical and photophysical properties of a family of Ir(III) complexes were studied through DFT/TD‐DFT calculations. The evaluated complexes have dppz‐based ligands containing electron‐donor substituents, therefore, the effect of substituents were analyzing in order to improve the radiative decay, proposing new luminescent materials with potential applications in light emitting electrochemical cells (LECs).